Comparison of diet quality on weekdays and weekends among high school students in a semi-military education system - Triatmoko, Barkah; Chandra, Dian Novita; Khusun, Helda (Indonesian Nutrition Association, 2024)
Adequate nutrition is critical for the growth, academic, and physical performance of adolescents. In semi-military schools, the regimented weekly schedules may influence students' eating patterns, potentially causing variations in diet quality between weekdays and weekends. This study aims to explore the differences in diet quality between weekdays and weekends among high school students enrolled in a semi-military education system.